Accuracy of the Horizontal Calibrator in Correcting Leg Length and Restoring Femoral Offset in Total Hip Arthroplasty - Chen, Xing; Xing, Shuxing; Zhu, Zhiyong; Wang, Huisheng; Yu, Zhongshen; Bai, Xizhuang; Li, Xi (Frontiers in Surgery, 2022)
Background: Limb length discrepancy (LLD) is one of the most common postoperative complications and can cause serious consequences. Poor recovery of femoral offset (OD) will result in weakness of the patient's external rotator muscles and affect the patient's postoperative function. The study is aimed to present a simple approach that compensates for the shortcomings of previous measuring devices and combines the advantages of different measuring devices to provide more accurate limb length and femoral offset restoration in total hip arthroplasty (THA). Methods: This study was a prospective controlled trial involving 89 patients with THA. The Group I (n = 44) was used for intraoperative measurement of THA with our self-designed Horizontal Calibrator. The Group II (n = 45) was measured by traditional freehand technique. The main outcome indicators were measured on the Neusoft PACS, including LLD, femoral offset deviation, and operative time. IBM SPSS 23.0 was used for data analysis. Results: The independent sample t-test was performed for all the data. The operative time, preoperative radiographic LLD and OD of the Group I and the Group II had no statistical significance. Postoperative LLD of the Group I and the Group II were 2.5±2.1 mm (range -5.7 mm to 8.3 mm) and 6.2±4.3 mm (range -18.0 mm to 15.2 mm) , and the independent sample t-test data of both (P<0.001; 95%CI=-5.1, -2.2) showed statistical significance. In the Group I, there were 38 THAs with LLD<5mm, accounting for 86%; there were 44 THAs with LLD<10mm, accounting for 100%. In the Group II, there were 20 THAs with LLD<5mm, covering for 44%. There were 36 THAs with LLD<10mm, covering for 80%. There was no significant difference in postoperative femoral offset and OD. Conclusion: The Horizontal calibrator can provide more accurate limb length and femoral offset recovery in THA. It is a simple surgical technique that does not add additionally surgical costs and does not significantly increase operative time, providing a new solution for surgeons to resolve postoperative LLD and restore femoral offset.